(untitled) (European Journal of Government and Economics, 2026)
This article investigates the dynamic interrelationships between the shadow economy, inflation, and economic growth in 15 countries of the Middle East and North Africa (MENA) region over the period 1991–2017. The study employs a simultaneous equations framework estimated through the Three-Stage Least Squares (3SLS) method, complemented by system GMM to address potential endogeneity issues. Empirical results reveal a bidirectional causal link between the shadow economy and inflation, highlighting their mutual reinforcement: the expansion of informal activities intensifies inflationary pressures by eroding public revenues and prompting monetary financing, while rising inflation encourages informal sector growth as agents seek protection against purchasing power erosion. Additionally, a two-way relationship between inflation and economic growth emerges, where moderate inflation can stimulate economic activity, but persistent high inflation hampers growth through price distortions and reduced real incomes. The shadow economy negatively impacts economic growth, with evidence showing that higher GDP levels reduce informality by expanding formal employment and compliance incentives. Nonetheless, the persistent size of the informal sector poses significant challenges for fiscal capacity and public investment, affecting infrastructure and social services. The robustness of these findings is confirmed through complementary estimation techniques. The article provides insights into the complex macroeconomic interactions characteristic of MENA economies, with important implications for policy aimed at promoting formalization, price stability, and sustainable growth.